2021
DOI: 10.1128/jcm.01295-20
|View full text |Cite
|
Sign up to set email alerts
|

Pooling of Nasopharyngeal Swab Samples To Overcome a Global Shortage of Real-Time Reverse Transcription-PCR COVID-19 Test Kits

Abstract: The global outbreak and rapid spread of SARS-CoV-2 created an urgent need for large scale testing of populations. There is a demand for high throughput testing protocols that can be used for efficient and rapid testing of clinical specimens. We evaluated a pooled-PCR protocol for testing nasopharyngeal swabs using known positive/negative and untested clinical samples that were assigned to pools of 5 or 10. Six-hundred and thirty (630) samples were used in this study. Individual positive samples with Ct values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Several approaches were developed to increase the throughput of qRT-PCR testing, e.g., sample pooling, which enables a shorter turnaround time with a slight reduction in test sensitivity [9][10][11][12][13][14], as well as using lysis buffer for swab collection instead of viral preservation medium [15]. While numerous studies were published on sample pooling [e.g., [9][10][11][12][13]], only a few studies were published on swab-pooling [16][17][18][19][20], with only one large-scale study [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches were developed to increase the throughput of qRT-PCR testing, e.g., sample pooling, which enables a shorter turnaround time with a slight reduction in test sensitivity [9][10][11][12][13][14], as well as using lysis buffer for swab collection instead of viral preservation medium [15]. While numerous studies were published on sample pooling [e.g., [9][10][11][12][13]], only a few studies were published on swab-pooling [16][17][18][19][20], with only one large-scale study [21].…”
Section: Introductionmentioning
confidence: 99%
“…More et al reported that while individual positive samples with high viral load (Ct < 28) were consistently detected in pools of 5 or 10 with other clinical samples, there was a higher frequency of false negatives when samples with lower viral loads (Ct >28) were pooled, especially in pools of 10. They showed that samples with individual Ct values >31 were not detected in pools of 10, whereas Ct values up to 33 could be detected in a pool of 5; they concluded that pooling up to five samples is more reliable for diagnostic purposes (61). Praharaj et al compared 5- and 10-sample pooling and showed that the former had higher concordance with individual testing and lower false-negative rates than the latter; they also showed that 10-sample pools had lower concordance with individual-sample testing, and higher false-negative rates at Ct values of more than 30 cycles (62).…”
Section: Discussionmentioning
confidence: 99%
“…More et al reported that while individual positive samples with high viral load (Ct < 28) were consistently detected in pools of 5 or 10, there was a higher frequency of false negatives when samples with lower viral loads (Ct > 28) were pooled, especially in pools of 10. They showed that samples with individual Ct > 31 were not detected in pools of 10, whereas Ct values up to 33 could be detected in a pool of 5; they concluded that pooling up to five samples is more reliable for diagnostic purposes [ 59 ]. Praharaj et al compared 5- and 10-sample pooling and showed that the former had higher concordance with individual testing and lower false-negative rates than the latter; they also showed that 10-sample pools had lower concordance with individual-sample testing, and higher false-negative rates at Ct > 30 [ 60 ].…”
Section: Discussionmentioning
confidence: 99%